2016
DOI: 10.4103/0974-2069.177516
|View full text |Cite
|
Sign up to set email alerts
|

Fetal left ventricular myocardial performance index: Defining normal values for Indian population and a review of literature

Abstract: Objective:The aim of this study was to determine normal values for fetal left ventricular (LV)-myocardial performance index (MPI) in Indian population and to assess its relation to advancing gestation and fetal heart rate (FHR).Materials and Methods:Two hundred pregnant women without any pregnancy-related complications and whose fetuses were shown to have structurally normal hearts were enrolled in this study. Doppler waveform involving simultaneous display of mitral inflow and LV outflow was obtained in all. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 18 publications
0
9
1
Order By: Relevance
“…Some studies have reported that it increases in advanced weeks of gestation while some other studies have argued that there is no such correlation and there is even a negative correlation. [12,16,17] In our study, we did not observe a significant increase in advanced weeks of gestation. When calculating Tei index, some authors measured ventricle entrance (mitral and tricuspid valves) and exit (aortic and pulmonary) pulsed Doppler records separately while some authors only measured time intervals that they obtained from a single Doppler record placed on an appropriate position.…”
Section: Discussioncontrasting
confidence: 69%
“…Some studies have reported that it increases in advanced weeks of gestation while some other studies have argued that there is no such correlation and there is even a negative correlation. [12,16,17] In our study, we did not observe a significant increase in advanced weeks of gestation. When calculating Tei index, some authors measured ventricle entrance (mitral and tricuspid valves) and exit (aortic and pulmonary) pulsed Doppler records separately while some authors only measured time intervals that they obtained from a single Doppler record placed on an appropriate position.…”
Section: Discussioncontrasting
confidence: 69%
“…It is a noninvasive Doppler‐derived indicator that evaluates global myocardial function . MPI has been proved to be a reliable parameter, not being affected by fetal cardiac ventricular size, fetal heart rate, and geometry . Some studies have demonstrated that FGR cases were associated with prenatal adverse cardiac remodeling .…”
Section: Introductionmentioning
confidence: 99%
“…6 MPI has been proved to be a reliable parameter, not being affected by fetal cardiac ventricular size, fetal heart rate, and geometry. 7,8 Some studies have demonstrated that FGR cases were associated with prenatal adverse cardiac remodeling. 9,10 The aim of this study was to investigate the changes of MPI in early-and late-onset FGR cases with different Doppler manifestations and its association with adverse perinatal outcome, to further confirm the clinical value of MPI in detecting and monitoring FGR.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, to the best of our knowledge, the assessment of fetal cardiac function is still evolving. The MPI has been proven to be independent of gestational age and the fetal heart rate, and the MPI can be used for the initial evaluation of global cardiac function in healthy fetuses and fetuses with congenital malformations . The IRT is the most important component of the MPI, and its derangement in the MPI indicates the earliest change in cardiac function impairment in diseased states .…”
Section: Discussionmentioning
confidence: 99%
“…The MPI has been proven to be independent of gestational age and the fetal heart rate, and the MPI can be used for the initial evaluation of global cardiac function in healthy fetuses and fetuses with congenital malformations. 15 The IRT is the most important component of the MPI, and its derangement in the MPI indicates the earliest change in cardiac function impairment in diseased states. 16 We found that fetuses with isolated mild-tomoderate VM before 32 weeks' gestation had not only a significantly higher Mod-MPI but also a longer IRT than the control group, whereas fetuses with isolated mild-to-moderate VM after 32 weeks' gestation only had a significantly longer IRT, with no significant difference in the Mod-MPI.…”
Section: Discussionmentioning
confidence: 99%